A SCOPING REVIEW OF NUTRITION AND DIET-RELATED FACTORS IN COMBATING LEPROSY DISEASE - Rusyda, Akifa Laila (Journal of Nutrition College, 2024)
ABSTRACTBackground: Indonesia still faces several challenges concerning the control of neglected tropical diseases (NTDs). Leprosy is one of the bacterial infectious NTDs caused by Mycobacterium leprae. The most obvious risk factors include undernutrition, poverty, food scarcity, food insecurity and a lack of food diversity. According to immunity beneficiaries and preventable or protecting factors, nutrition and food are essential.Objectives: To synthesize the diet and nutrition risk factors and consequences with the most substantial evidence related to leprosy disease.Methods: Five databases were searched systematically, following punctuation and conventions-based keyword searches and criteria and free-text terms. Selected articles included systematic reviews and other studies involving human subjects published between 2013 and 2023. Finding articles (n=588) were interpreted using preferred reporting of items for systematic reviews and meta-analyses (PRISMA). Eligible articles (n=16) were described by author’s name, publication year, study objectives, locations, study design, participants, methods, intervention and exposure, and critical findings and impacts/outputs.Results: In 16 studies, there were nutrition explanations correlated to leprosy disease. Malnutrition, either undernutrition or overnutrition, may lead to a worse disease prognosis. A comprehensive approach to food security, diet quality, and dietary behaviors is needed to protect against the disease. Affected individuals tend to have lower essential nutrition serum levels to obtain multiple micronutrient supplements such as vitamins A, C, D, E, zinc and selenium.Conclusion: Regarding immunity beneficiaries and impacted factors, there are several potential risk factors related to nutrition and diet in leprosy that are necessary considerations, including nutritional status, food and nutritional security (food environment-related) and dietary behavior. Keywords: Food insecurity; Immune responses; Leprosy; Neglected tropical disease; Nutrition vulnerability.